PENGEMBANGAN PENUNTUN PRAKTIKUM BERBASIS PjBL TERHADAP KETERAMPILAN PROSES SAINS SISWA - Huda, Muhammad Komarul; Damanik, Risjunardi; Aldi, Muhammad (Jurnal Metabio, 2024)
This research aims to determine the feasibility of PjBL-based practicum guidance on students' science process skills and to determine the results of students' science process skills scores. The research population was 224 students consisting of 7 classes at SMP N 7 Pematang Siantar for the 2023/2024 academic year. The research sample was 32 students consisting of 1 class, the sample was taken using a cluster random sampling technique. The results of the feasibility of the practicum guide are measured using expert validation sheets and student response questionnaires. The results of students' science process skill scores are measured using observation sheets. Furthermore, the data obtained from the expert validation sheet is 93% ecologist with a very feasible category, 89% material expert with a very feasible category. The student response was 91% in the very good category, the application score was 86% in the very good category, and the students' science process skills score was 75% in the good category